Variation of Dst in the American meridional sector - Melnik, G. V.; Jaremenko, L. N. (Ukrainian Antarctic Journal, 2004)
Magnetic storms occurring in the equatorial Earth’s belt, where the Dst variation is mainly manifested, and in meridional sections of the American, Euro-African and Australia-Far East sectors were considered. The differences in the initial phase of the magnetic storm for different observatories depend on longitude and may be associated with the time of the shock wave arrival. The criteria distinguishing the Dst and polar substorms were their latitudinal dependence with max Dst and with the minimal substorm amplitudes at the equator. The special Dst-samples were detected in Europe, Asia, Africa, and Australia observatories. In America observatories an unusually strong S-ward Dst maximum shift (to 40°s) was found. This case cannot be explained by the S-ward magnetic equator shift. Further South, at Academic Vernadsky Dst variations are not observed, though they occur at the same geographic latitude in North Europe. An unusual Dst peculiarities are seen at the San-Juan observatory where Dst is usually less than the normal one, while at the observatory Curu and the other Southernmost observatories of North America it coincides with predicted values. Abnormal Dst and magnetic substorms are observed at the mid-latitude Fredericksburg and Ottawa stations.